Evaluation of the rapid and slow maxillary expansion using cone-beam computed tomography: a randomized clinical trial - Juliana da S. Pereira; Helder B. Jacob; Arno Locks; Mauricio Brunetto; Gerson L. U. Ribeiro
ABSTRACT OBJECTIVE: The aim of this randomized clinical trial was to evaluate the dental, dentoalveolar, and skeletal changes occurring right after the rapid maxillary expansion (RME) and slow maxillary expansion (SME) treatment using Haas-type expander. METHODS: All subjects performed cone-beam computed tomography (CBCT) before installation of expanders (T1) and right after screw stabilization (T2). Patients who did not follow the research parameters were excluded. The final sample resulted in 21 patients in RME group (mean age of 8.43 years) and 16 patients in SME group (mean age of 8.70 years). Based on the skewness and kurtosis statistics, the variables were judged to be normally distributed and paired t-test and student t-test were performed at significance level of 5%. RESULTS: Intermolar angle changed significantly due to treatment and RME showed greater buccal tipping than SME. RME showed significant changes in other four measurements due to treatment: maxilla moved forward and mandible showed backward rotation and, at transversal level both skeletal and dentoalveolar showed significant changes due to maxillary expansion. SME showed significant dentoalveolar changes due to maxillary expansion. CONCLUSIONS: Only intermolar angle showed significant difference between the two modalities of maxillary expansion with greater buccal tipping for RME. Also, RME produced skeletal maxillary expansion and SME did not. Both maxillary expansion modalities were efficient to promote transversal gain at dentoalveolar level. Sagittal and vertical measurements did not show differences between groups, but RME promoted a forward movement of the maxilla and backward rotation of the mandible.